2002
DOI: 10.1021/ic025851h
|View full text |Cite
|
Sign up to set email alerts
|

From Metallacyclophanes to 1-D Coordination Polymers:  Role of Anions in Self-Assembly Processes of Copper(II) and 2,5-Bis(3-pyridyl)-1,3,4-oxadiazole

Abstract: The reaction of various CuII salts with 2,5-bis(3-pyridyl)-1,3,4-oxadiazole (L) in CH3CN-H2O medium affords different complexes, the solid structures of which are controlled only by the choice of the counteranions. Reaction of Cu-(ClO4)2.6H2O or Cu(NO3)2.3H2O and L yields the novel bimetallic macrocyclic complex [Cu2L2(H2O)6](ClO4)4(H2O)4 (1) [monoclinic, space group P21/m, a = 8.745(5) A, b = 16.179(10) A, c = 14.930(8) A, beta = 93.253(10) degrees, Z = 2] or [CuL(NO3)2]2(CH3CN)2 (2) [triclinic, space group P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
30
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(34 citation statements)
references
References 58 publications
4
30
0
Order By: Relevance
“…7 The ESI mass spectrum shown in Fig. 1 17 We also found that formation of this complex in the gas phase does not take place when another copper salt ( Fig. 2(a)) or another solvent is used ( Fig.…”
mentioning
confidence: 68%
See 2 more Smart Citations
“…7 The ESI mass spectrum shown in Fig. 1 17 We also found that formation of this complex in the gas phase does not take place when another copper salt ( Fig. 2(a)) or another solvent is used ( Fig.…”
mentioning
confidence: 68%
“…[1][2][3][4][5][6][7][8] Because of the wide spectrum of biological activity of 1,3,4-oxadiazoles, their copper complexes have attracted much attention. [9][10][11][12][13][14][15][16][17] It has been shown that 2,5-bis(2-pyridyl)-1,3,4-oxadiazole forms 2:1 copper complexes 9,11 and that 2,5-bis(3- (Fig. 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As we know, anions play important roles in the formation of coordination polymers. For example, some anions, such as X − , NO 3 − , and CH 3 COO − with strong coordination ability can coordinate to metal ions or bridge metal centers to generate multi-nuclear units or high-dimensional frameworks [15][16][17][18], but some other anions, such as PF 6 − , ClO 4 − , BF 4 − , and CF 3 SO 3 − possess very weak coordination ability and usually act as counterions and templates in the formation of the products [19][20][21]. Although many studies on anion-controlled formation of coordination polymers have been reported, very few examples of anion effect on the photochromic properties of coordination polymers have been involved so far because it is usually difficult to create appropriate coordination polymers with photochemical activity, but also containing different anions [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Aromatic-aromatic or p-p stacking interaction is one of the important types of non-covalent intermolecular forces similar to hydrogen bonding and has been recognized to play a key role in the stabilization and regulatory functions of both biological systems and supramolecular construction, where it contributes significantly to self-assembly and molecular recognition processes [11][12][13]. However, in contrast to the wellunderstood hydrogen bonding interaction, the nature and utilization of p-p interaction, mainly for further development of supramolecular chemistry and prediction of crystal structures, is still not well documented [14].Recently, we have initiated a research program for the construction of various supramolecular architectures with interesting extended frameworks based on a designed angular dipyridyl ligand, 2,5-bis(4-pyridyl)-1,3,4-oxadiazole (bpo) and its 3-pyridyl isomer [15][16][17][18]. The role of subtle controlling factors, especially the use of counter anions, of the self-assembly processes in the formation of these novel coordination polymers or supermolecules was investigated in detail.…”
mentioning
confidence: 99%